2021
DOI: 10.3390/vaccines9060556
|View full text |Cite
|
Sign up to set email alerts
|

Side Effects and Perceptions Following COVID-19 Vaccination in Jordan: A Randomized, Cross-Sectional Study Implementing Machine Learning for Predicting Severity of Side Effects

Abstract: Background: Since the coronavirus disease 2019 (COVID-19) was declared a pandemic, there was no doubt that vaccination is the ideal protocol to tackle it. Within a year, a few COVID-19 vaccines have been developed and authorized. This unparalleled initiative in developing vaccines created many uncertainties looming around the efficacy and safety of these vaccines. This study aimed to assess the side effects and perceptions following COVID-19 vaccination in Jordan. Methods: A cross-sectional study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

42
181
8
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(234 citation statements)
references
References 49 publications
42
181
8
3
Order By: Relevance
“…Additionally, the side effects were more severe among AstraZeneca-Oxford vaccine recipients ( P value < 0.0001). In line to the present study, a study from Jordan, a neighboring country, found that the number and severity of side effects were associated with the type of vaccine [ 21 ]. Another study by Mathioudakis et al.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, the side effects were more severe among AstraZeneca-Oxford vaccine recipients ( P value < 0.0001). In line to the present study, a study from Jordan, a neighboring country, found that the number and severity of side effects were associated with the type of vaccine [ 21 ]. Another study by Mathioudakis et al.…”
Section: Discussionsupporting
confidence: 87%
“…Most of studies have assessed mainly the post-vaccination adverse reactions of the Pfizer–BioNTech, Moderna, and Astrazeneca vaccines ( Kadali et al, 2021 , Chapin-Bardales et al, 2021 , Menni et al, 2021 , Riad et al, 2021 , El-Shitany et al, 2021 ), while only two studies focus on Sinopharm COVID-19 vaccine ( Jayadevan et al, 2021 , Hatmal et al, 2021 ), There are no published studies yet that have focused on Sinopharm COVID-19 vaccine side effects in UAE.…”
Section: Discussionmentioning
confidence: 99%
“…Injection site pain symptom reported in several literatures on vaccines’ side effects ( Jayadevan et al, 2021 , Hatmal et al, 2021 , Riad et al, 2021 , El-Shitany et al, 2021 ), injection in a relaxed muscle leads to less pain compared to a tensed one; therefore, the researchers recommended to lower the patient's arm that will be injected to reduce the pain. In addition, vaccines in in situ should be keep it in a low temperature, including Sinopharm COVID-19 vaccine that should store at normal refrigeration temperature, and if injected without optimal warming up, this may increase the probability of pain of the injection site symptom.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations